Peran Kualitas Integrasi Omnichannel dalam Membentuk Niat Perilaku Generasi Y & Z - Agung, Deatri Arumsari; Purwanto, Gabriella Lisbeth Avriel; Ellitan, Lena (Ekonomis: Journal of Economics and Business, 2024)
This research aims to understand the omnichannel shopping behavior of the Y and Z generations, by focusing on the role of customer involvement in mediating the influence of omnichannel integration quality on behavioral intentions, and examining the role of age in moderating the influence of customer involvement. This quantitative research uses a Likert scale, where the total number of questionnaires obtained and processed was 204 samples. This research was conducted in Surabaya with respondents from Surabaya and its surroundings. Data analysis was carried out using PLS-SEM technique, with the SmartPLS3 analysis tool. The three dimensions of omnichannel integration quality, namely channel-service configuration, integrated interactions, and assurance quality, are proven to have a positive influence on customer engagement. Customer involvement is proven to influence behavioral intentions positively, and mediate the influence of omnichannel integration quality three dimensions on behavioral intentions. Age is also proven to have a moderating role that strengthens the influence of customer involvement on behavioral intentions. One managerial implication is that generation Y should be of greater concern in efforts to develop customer engagement, compared to generation Z, to maximize customers' behavioral intentions.